Restriction of the official’s discretion competence as an anti-corruption tool - Linhartová, Veronika (Univerzita Pardubice, 2016)
As a possible tool for reducing opportunities for corrupt behavior of public officials in the public sector, a lot of studies have shown that this could be done through easy access to information for all citizens through the use of e-government. This paper analyzes the potential role of e-Government in reducing corruption by examining the impact of the use of e-Government on the level of corruption in 117 countries in the period 2003-2014. Used correlation and regression confirmed the possible reduction of the level of corruption in a country through the use of e-Government for economically developed countries, but for economically not so developed countries as well. A one percent increase of the use of e-Government led to reduction of the level of corruption by 0,12 % for the most economically developed countries. A one percent increase of the use of e-Government caused corruption reduction by 0,14 % for the least economically developed countries. Thus, in fact cannot be a panacea for fighting corruption in all countries, political regimes and government establishment, whereas, the use of e-Government should be considered as an opportunity to reduce corruption.
Omezování diskreční pravomoci úředníků jako protikorupční nástroj
Keywords: Official´s Discretion Competence; Anti-corruption Tool; Corruption; Corruption Perception Index; E-Government Development Index; Diskreční pravomoc úředníka; protikorupční nástroj; korupce; Index vnímání korupce; E-Government development index